Web Based System For The Organization Of Cultural Events And Interactions : For Student Affairs Department (HEP) - UUM - Alnogga, Ibrahim Abdelhafiez A (2008)
Internet is now considered a mass medium of connectivity and sharing, it has become a topic of research and studies because of its implications for societies. The Internet can promote a better understanding between cultures and cultural identities by enabling people from different cultural backgrounds and with different social and cultural identities to come together and communicate with each other under helpful conditions for cultural exchange. This study attempts to introduce a fully cultural-oriented website for organizing cultural events, activities, and interactions among students in a given university. UUM was chosen as the object community for using this website, the website is to be controlled by staff from the Student Affairs Department (HEP), the developed site was evaluated through a distributing a questionnaire for 43 users; the results showed that the users found the web application practical and useful.